Money, markets, and sovereignty - Steil, Benn.; Hinds, Manuel (New Haven : Yale University Press, 2009)
This book is an important analysis of the roles of money and sovereignty in advancing globalization and its positive effects on living standards. Particularly in this era of political skepticism over gains from globalization, the authors have written an essential text for our new leaders and those who advise them.
Thinking about money and globalization -- A brief history of law and globalism -- The anti-philosophy of anti-globalism -- A brief history of monetary sovereignty -- Globalization and monetary sovereignty -- Monetary sovereignty and gold -- The future of the dollar -- The shifting sands of sovereignty.
"A Council on Foreign Relations book."
Includes bibliographical references (p. [263]-275) and index.
rpm 17/05/13
Loans
Keywords: Money; Globalization -- Economic aspects; Monetary policy